SURVEY OF MALOCCLUSION STATUS AND ORTHODONTIC TREATMENT NEEDS AMONG STUDENTS OF HANOI UNIVERSITY OF BUSINESS AND TECHNOLOGY (Vietnam Journal of Community Medicine, 2026)
Objective: To describe malocclusion status and assess orthodontic treatment need among Hanoi University of Business and Technology’ students in 2022.Subjects and methods: The study was conducted among 215 students aged 18-24 years at Hanoi University of Business and Technology from February to August 2022 using a cross-sectional descriptive design. Purposive convenience sampling was applied. Occlusion status was classified according to Angle’s method on plaster models, and orthodontic treatment needs were assessed using the IOTN index.Results: Malocclusion was identified in 65.1% of participants, with class I malocclusion being the most prevalent at 47.9%. Tooth displacement greater than 1 mm was the most common contributing factor, recorded in 64.7% of cases. Based on the aesthetic component of the IOTN, 26.5% of students required or strongly required orthodontic intervention (grades 5-10). Assessment using the dental health component indicated that 44.7% had treatment indications at grades 3-5. No statistically significant differences were observed in treatment need between sexes or between the two IOTN components.Conclusion: The much higher demand for dental health component treatment compared to aesthetic component treatment suggests that malocclusion in college students primarily affects function rather than aesthetics, and this need should be prioritized in oral care for college students.
Keywords: Malocclusion, orthodontic treatment need, IOTN index, university students.